2009
DOI: 10.1007/s10545-009-1082-3
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme analysis for Pompe disease in leukocytes; superior results with natural substrate compared with artificial substrates

Abstract: Enzyme analysis for Pompe disease in leukocytes has been greatly improved by the introduction of acarbose, a powerful inhibitor of interfering alpha-glucosidases, which are present in granulocytes but not in lymphocytes. Here we show that the application of acarbose in the enzymatic assay employing the artificial substrate 4-methylumbelliferyl-alpha-D: -glucoside (MU-alphaGlc) is insufficient to clearly distinguish patients from healthy individuals in all cases. Also, the ratios of the activities without/with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…However, the existence of pseudo deficiency mutations increases the likeliness of false positive results being obtained (Diggelen et al 2009). The finding that Glc 4 is only marginally elevated when compared to untreated Pompe patients raises the possibility that urinary Glc 4 measurements may be a useful adjunct to a diagnostic enzyme service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the existence of pseudo deficiency mutations increases the likeliness of false positive results being obtained (Diggelen et al 2009). The finding that Glc 4 is only marginally elevated when compared to untreated Pompe patients raises the possibility that urinary Glc 4 measurements may be a useful adjunct to a diagnostic enzyme service.…”
Section: Discussionmentioning
confidence: 99%
“…However, for some patients significant residual GAA activity can make the definitive diagnosis of Pompe disease difficult (van Diggelen et al 2009). In recent years, a new method has been developed to allow the rapid determination of GAA (+/− acarbose) in dried blood spots.…”
Section: Introductionmentioning
confidence: 99%
“…The test result should always be considered in combination with other results—for example, creatine kinase (CK), alanine aminotransferase (ALAT), and aspartate aminotransferase (ASAT) (Winkel et al 2005)—and a careful clinical examination. On the other hand, when a high percentage of PAS-positive lymphocyte vacuoles is found, further testing by measuring acid α-glucosidase activity in leukocytes (van Diggelen et al 2009) is always indicated. This fits into previously proposed diagnostic algorithms for childhood- and adult-onset Pompe disease (Straub 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…Milder forms of the disease may present at any age, with limb-girdle weakness as the most prominent clinical feature (Hirschhorn and Reuser 2000; van der Ploeg and Reuser 2008). The diagnosis of Pompe disease is confirmed by measuring acid α-glucosidase activity in leukocytes using the latest optimized procedures, or in cultured fibroblasts (Hirschhorn and Reuser 2000; van Diggelen et al 2009; Winchester et al 2008). These tests, however, are carried out in a specialized laboratory and are usually not applied unless there is already a strong suspicion for Pompe disease.…”
Section: Introductionmentioning
confidence: 99%
“…The GAA activity in leukocytes was measured with glycogen as substrate in the presence of acarbose to inhibit the glucoamylase activity (Glyc + ACAB) in accordance with previously described procedures [17,18]. The GAA activity in fibroblasts and muscle was measured with 4-methylumbelliferyl-α-D-glucopyranoside (4-MU) and/or glycogen as substrates [8].…”
Section: Enzyme Analysis and Glycogen Contentmentioning
confidence: 99%